2013
DOI: 10.1182/blood-2013-03-488486
|View full text |Cite
|
Sign up to set email alerts
|

DEPTOR regulates vascular endothelial cell activation and proinflammatory and angiogenic responses

Abstract: Key Points• DEPTOR is expressed in vascular endothelial cells and serves as an endogenous inhibitor of mTORC1, ERK1/2, and STAT1 activity.• DEPTOR is potent to regulate endothelial cell expression of chemokines and adhesion molecules, leukocyte-endothelial adhesion, and endothelial migratory responses.The maintenance of normal tissue homeostasis and the prevention of chronic inflammatory disease are dependent on the active process of inflammation resolution. In endothelial cells (ECs), proinflammation results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 49 publications
(59 reference statements)
2
48
0
Order By: Relevance
“…Our study also revealed that expression of P-S6 (S235/236) was significantly higher in CRC tissue than in normal colorectal mucosa (p<0.01). When greatly overexpressed, DEPTOR inhibits mTORC1 (Peterson et al, 2009;Bruneau et al, 2013;Meng et al, 2013;Zhang et al, 2013). In this study, DEPTOR was equally expressed in CRC and adjacent DOI:http://dx.doi.org/10.7314/APJCP.2014.15.11.4589 DEPTOR Expression Negatively Correlates with mTORC1 Activity and Tumor Progression in Colorectal Cancer normal colorectal mucosa.…”
Section: Discussionmentioning
confidence: 83%
“…Our study also revealed that expression of P-S6 (S235/236) was significantly higher in CRC tissue than in normal colorectal mucosa (p<0.01). When greatly overexpressed, DEPTOR inhibits mTORC1 (Peterson et al, 2009;Bruneau et al, 2013;Meng et al, 2013;Zhang et al, 2013). In this study, DEPTOR was equally expressed in CRC and adjacent DOI:http://dx.doi.org/10.7314/APJCP.2014.15.11.4589 DEPTOR Expression Negatively Correlates with mTORC1 Activity and Tumor Progression in Colorectal Cancer normal colorectal mucosa.…”
Section: Discussionmentioning
confidence: 83%
“…The main reason is that mTORC1 may have a more important role in angiogenesis than mTORC2 according to the previous studies. In addition, a recent study found that knockout of DEPTOR did not significantly affect the activity of Akt [18]. This means that loss of DEPTOR has no obvious effect on the mTORC2 pathway.…”
Section: Discussionmentioning
confidence: 93%
“…One study reported that DEPTOR regulates vascular EC activation and contributes to proinflammatory and angiogenic responses in vitro [18]. Our study examined the role of DEPTOR during angiogenesis in vivo and elucidated the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggested an interaction between the mTOR-dependent metabolic state and the inflammatory properties of endothelial cells. 13 We now found a significant induction of endothelial autophagy after overexpression of miR-100 ( Figure 3A-3C), whereas inhibition of this microRNA led to a significant reduction of LC3B-positive Figure 2. Regulation of endothelial adhesion molecule expression is mammalian target of rapamycin complex 1 (mTORC1) dependent.…”
Section: Stimulation Of Endothelial Autophagy After Overexpression Ofmentioning
confidence: 99%